A Multidimensional Concept of Meaningful Work: Theoretical Framework - Iždonaitė-Medžiūnienė , Inga; Batuchina, Aleksandra (Social Welfare: Interdisciplinary Approach, 2023)
The article focuses on the multidimensional concept of meaningful work and the concept of its theoretical framework. Scientific literature presents meaningful work models related to several areas as multi-dimensional or even one area as uni-dimensional. Uni-dimensional models as presented in earlier research allow revealing experiences without specifying them, rather to help capture people’s global judgment of the extent to which their work is meaningful. We argue that multidimensional models covering a wide range of areas are purposeful in order to comprehensively study meaningful work and identify significant specific experiences. The completed scientific research analysis allowed us to highlight the core dimensions of a meaningful work concept and form a theoretical framework for further testing. Such multidimensional composition of meaningful work shows a holistic approach and provides a universal instrument for the evaluation of meaningful work at any organizational level and field.